Exploring the barriers to diagnosing malnutrition in patients with cancer: A study on oncologists' perspectives - Lisa Heide Koteng; Kari Sand; Ingvild Paur; Asta Bye; Bente Ervik; Tora S. Solheim; Inger Ottestad; Trude R. Balstad (Clinical Nutrition Open Science)
Summary: Background and aim: Patients with cancer are at high risk of malnutrition, yet relevant ICD-10 codes for malnutrition are underutilized in cancer clinics. Understanding oncologists' perspectives is crucial for optimizing malnutrition diagnosis codes and enhancing nutritional practices to improve patient care. This study aims to explore oncologists' perspectives on the use and feasibility of the ICD-10 codes for malnutrition. Methods: A qualitative study was conducted, consisting of four focus group interviews with oncologists (n=14) from three Norwegian hospitals. A semi-structured interview guide, covering five main topics, guided the discussions. Results: Few oncologists were familiar with the malnutrition diagnosis codes. The codes were considered inapplicable in clinical practice, partly due to complex diagnostic criteria. None used the codes systematically, instead relying on inquiries about patients' weight, weight loss, food intake, and appetite. Oncologists prioritized identifying patients in need of nutritional treatment, considering diagnosis codes unnecessary for providing quality care. Proposals for increased code utilization included economic incentives, enhanced collaboration with clinical dietitians, and digital systems for automated coding. Conclusion: The oncologists expressed that they prevent and treat malnutrition in patients with cancer, but not systematically. They do not utilize ICD-10 codes for malnutrition, citing both complex diagnostic criteria and the codes’ lack of relevance to nutritional treatment as limiting factors.